Integrating HR Management and Digital Talent Management to Enhance Organizational Competitiveness: Evidence from Local Government Agencies - Chrismesi Pagiu; Westerini Lusdani; Ellyn Patadungan (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Digital transformation is reshaping public sector organizations, necessitating enhanced competitiveness through advanced technologies and optimised human resource strategies. This study aims to determine the effect of human resource management and digital talent management practices on public organizational competitiveness, focusing on their individual and combined effects. A quantitative approach employing Partial Least Squares Structural Equation Modelling was used, with data collected from 380 government employees in a local region via a survey. Human Resource Management significantly strengthens competitiveness by enhancing workforce capabilities, motivation, and commitment (β=0.38; p<0.05), while Digital Talent Management drives innovation and organizational flexibility (β=0.42; p<0.05). The integration of both practices yields the strongest impact (β=0.71; p<0.05), highlighting their synergistic effect. The findings underscore that sustainable competitiveness in public organizations relies on integrating human resource management with digital talent management. Local governments should adopt policies that align these frameworks to foster adaptive, innovative, and citizen-oriented governance, ensuring effective bureaucratic transformation in the digital era. This study enriches theoretical discourse and offers practical guidance for enhancing public sector performance.